Productive Consumption and Growth in Developing Countries - Thomas Steger (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1997)
Productive consumption enables the satisfaction of current needs and, at the same time, increases the productive potential of labour. Theoretical as well as empirical evidence suggests that productive consumption is primarily relevant to low-income countries. From the perspective of growth theory, the productive-consumption hypothesis is of fundamental interest because it modifies the "harsh" intertemporal consumption trade-off traditionally assumed. The incorporation of the productive-consumption hypothesis into a simple endogenous growth model reveals the following implications: (a) the possibility of a poverty-trap, (b) the rule of optimal consumption turns into a modified Keynes-Ramsey rule, (c) the (effective) IES is not only based on preferences but in addition on the technological possibilities to enhance human capital due to productive consumption, (d) a rising saving rate, and (e) transitional dynamics to an asymptotic balanced growth equilibrium.
Keywords: 330